Actitud hacia wordwall en estudiantes de secundaria, Chupaca – Perú – 2022 - Utos-Barrantes, Uber E (2024)
This research deals with the "Attitude towards Wordwall", which is understood as the evaluations, assessments or judgments that users have and/or make about this tool; for which it was proposed as an objective to determine the attitude towards the digital tool Wordwall in second grade high school students of the educational institution Jorge Basadre de Chupaca - Junín - Peru. It is a basic and descriptive research, with a non-experimental design of simple descriptive cross-sectional type. We worked with a census sample of 84 students in the second grade of secondary school, to whom a 21-item questionnaire was applied unannounced and only once. The following results were found: 1) 8.33% of the respondents showed an indifferent attitude towards Wordwall, while 91.67% showed a favorable attitude. 2) 92.86% show a favorable cognitive attitude. 3) 85.71% show a favorable affective attitude. 4) 86.90% show a favorable Behavioral attitude. It is concluded that the attitude towards Wordwall is favorable in second year high school students of the Jorge Basadre School in Chupaca - Junin - Peru.